The relationship between health and growth: When Lucas meets Nelson-Phelps - Philippe Aghion; Peter Howitt; Fabrice Murtin (Bruegel, 2010)
This paper revisits the relationship between health and growth in light of modern endogenous growth theory. We propose a unified framework that encompasses the growth effects of both the rate of improvement of health and the level of health. Based on cross-country regressions over the period 1960-2000, we find that a higher initial level and a higher rate of improvement in life expectancy both have a significantly positive impact on per capita GDP growth. Then, restricting attention to OECD countries, we find supporting evidence that only the reduction in mortality below age forty generates productivity gains, which in turn may explain why the positive correlation between health and growth in cross-OECD country regressions appears to have weakened since 1960.
Keywords: 330; Neue Wachstumstheorie; Gesundheit; Sterblichkeit; Sozialprodukt; Wirtschaftswachstum; Regression; OECD-Staaten